A Bibliometric Analysis Using VOSviewer on the Concept of “Tax Privacy/Confidentiality” and Prominent Themes - AKYOL BULUT, Öznur; GÖKBUNAR, Ramazan (International Journal of Contemporary Economics and Administrative Sciences, 2025)
This study conducts a bibliometric analysis of the concept of tax privacy using data from the Web of Science (WoS) database and analyzes those data with VOSviewer visualization software. The objective is to map the intellectual structure, thematic evolution, and research trends in the field of tax privacy, a niche yet increasingly relevant topic at the intersection of law, information systems, and fiscal governance. The analysis covers 401 publications indexed between 1972 and 2025, primarily in the Social Sciences Citation Index (SSCI), the Emerging Sources Citation Index (ESCI), and the Science Citation Index Expanded (SCIE). The Findings indicate a significant rise in scholarly output after 2000, with a sharp increase after 2020, reflecting the growing integration of digitalization and data protection into fiscal systems. Most of the studies were published in the fields of law (89), computer and information sciences (65), and economics (68). Co-authorship and citation network analyses reveal that Miltgen, Popovic, and Oliveira are the most cited, with 301 citations, whereas Burman and Leonard are the most productive and most collaborative. Keyword co-occurrence mapping highlights key research clusters centered on privacy, blockchain, security, cryptocurrency, data protection, e-government, and tax evasion, demonstrating the convergence between tax confidentiality and emerging digital technologies. The results underline the increasing importance of tax privacy as a multidisciplinary research field, linking technological innovation, legal design, and ethical data governance. The study provides a foundational map for future research into protecting taxpayer data in evolving digital tax ecosystems.